Role of Ultrasound Evaluation of Temporomandibular Joint in Juvenile Idiopathic Arthritis: A Systematic Review - Achille Marino; Orazio De Lucia; Roberto Caporali (MDPI AG, 2022)
Background: Juvenile idiopathic arthritis (JIA) is childhood's most frequent chronic rheumatic disease. JIA is a broad term that includes all arthritides starting before 16 years, lasting at least six weeks, and of unknown cause. The temporomandibular joint (TMJ) could be involved in JIA both at onset and during the disease course. The presence of TMJ synovitis might severely impair dentofacial maturation in pediatric patients. The ultrasound (US) application to detect early signs of TMJ synovitis in children with JIA has provided contradictory results. We sought to assess the current role of TMJ US in JIA through a systematic literature review. Methods: The systematic review was conducted according to the recommendations of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Results: The literature search found 345 records. After duplicates removal, 253 records were screened, 20 full-text articles were reviewed to assess their eligibility, and 7 of them were included in the qualitative analysis. Joint effusion was the most recorded parameter, followed by bony condylar abnormalities. Compared to contrast enhancement MRI, the capability to detect signs of active synovitis of TMJ by US is low, especially at the early stages. Conclusion: Understanding how US may help diagnose and manage children with JIA is advisable for several reasons. MRI cannot be frequently repeated, may need sedation, and is expensive. The constant technical improvement of US will undoubtedly allow for better evaluation of what, in the past, was not clear or not even captured by sonography. So far, the role of US in the assessment of TMJ involvement in JIA is indubitably secondary to the MRI. Even so, we think that a baseline MRI of TMJ and the repetition of the sonography over time might both help the interpretation of US images and intercept significative changes.